Comparative cost analysis of inpatient integrative medicine—Results of a pilot study. (June 2017) - Ostermann, Thomas; Lauche, Romy; Cramer, Holger; Dobos, Gustav
Highlights: This study for the first time presents results of a comparative cost analysis of inpatient integrative medicine treatment including 1253 patients. In-house comparisons with other departments found the department close to departments of Internal medicine. Interhospital comparison revealed a comparable Casemix-Index and DRG-revenue. In conclusion modern integrative in-patient treatment is mostly cost-equivalent to conventional treatment. Abstract: Background: Costs of integrative treatment alone and in comparison with other treatment approaches have scarcely been reported in the past. This study presents results of a comparative cost analysis of an inpatient integrative medicine treatment costs. Methods: Data from 2006 for inpatients referred to a Department of Integrative Medicine in Germany were used. Case-related treatment costs were calculated, and transformed into Casemix-Indices and revenues per DRG. Costs were compared between departments at the same hospital and between different hospitals using univariate statistics and Chi-Square tests. Results: In total 1253 inpatients (81.4% female, 61.1 ± 14.4 years) were included in the current analysis. Most patients were treated for diseases of the musculoskeletal system (57.2%), followed by diseases of the digestive system (11.4%), and diseases of the nervous system (10.4%). The department received an additional payment for most of the patients (88.0%), which led to an effective appreciation of 10.8% per case compared to the standardized Casemix-Index. In-house comparisons with other departments found the department in close vicinity to the departments of Internal medicine with regards to CMI and mean revenue, however the Patient Clinical Complexity Level was significantly lower in the Integrative medicine department. The interhospital comparison revealed comparable Casemix-Index and DRG-revenue, however the additional payment increased the mean revenue significantly. Conclusion: Modern integrative in-patient treatment is mostly cost-equivalent to conventional treatment. Cost effectiveness studies should be considered to further investigate the potential of integrative in patient treatment.